2010
DOI: 10.1510/icvts.2009.219576
|View full text |Cite
|
Sign up to set email alerts
|

Is transcutaneous electrical nerve stimulation effective in relieving postoperative pain after thoracotomy?

Abstract: A best evidence topic was constructed according to a structured protocol. The question addressed was whether the use of transcutaneous electrical nerve stimulation (TENS) is effective in reducing post-thoracotomy pain. Of the 74 papers found with a report search, nine prospective randomized controlled trials (RCT), among which three were double-blind, presented the best evidence to answer the clinical question. All investigated the effect of TENS as an adjunct therapy for relieving acute post-thoracotomy pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 9 publications
6
33
0
4
Order By: Relevance
“…The number (proportion) of patients reporting severe posterior neck pain (NRS ≥ 7) at any time point was two (4%) in the TENS group compared with six (12%) in the control group, but this did not reach statistical significance. Our results support the findings of other studies that TENS is useful to treat mild to moderate postoperative pain [16].…”
Section: Discussionsupporting
confidence: 92%
“…The number (proportion) of patients reporting severe posterior neck pain (NRS ≥ 7) at any time point was two (4%) in the TENS group compared with six (12%) in the control group, but this did not reach statistical significance. Our results support the findings of other studies that TENS is useful to treat mild to moderate postoperative pain [16].…”
Section: Discussionsupporting
confidence: 92%
“…The first meta-analysis on TENS was conducted in 2003 and found that TENS reduced post-operative consumption of analgesic medication to a greater extent than placebo when TENS was administered using appropriate technique [5]. More recent systematic reviews confirm the efficacy of TENS for post-thoracotomy and post-sternotomy pain [8,9]. The most recent Cochrane review on TENS on acute pain in adults included 19 RCTs (1346 participants) of procedural (cervical laser treatment, venepuncture, screening flexible sigmoidoscopy) and non-procedural pain (postpartum uterine contractions and rib fractures) [10].…”
Section: Editorialmentioning
confidence: 99%
“…Akut torakotomi ağrısında epidural anesteziye ek olarak uygulanan TENS'in, ağrı şiddetini azalttığı, hastaların sistolik kan basınçlarını düşüre-rek hemodinamik stabilitelerini sağladığı bulunmuştur (57). Akciğer rezeksiyonunda posterolateral torakotomi sonrası TENS'in orta ve hafif ağrıda etkili, şiddetli ağrıda etkisiz olduğu saptanmıştır (58). Posterolateral torakotomi hastalarında TENS'in, plasebo TENS veya hasta kontrollü analjezi uygulamalarına göre istirahatte ve öksürme sırasında ağrı şiddetini, analjezik kullanı-mını azalttığı ve hastaların solunum fonksiyonlarında gelişmeler meydana getirdiği kanıtlanmıştır (56,59).…”
Section: Ağrı Kontrolüunclassified
“…İlgili araştırmalara göre TENS; toraks cerrahisi sonrası akut ve kronik posterolateral torakotomi ağrısını azaltarak, PR programlarına hastanın aktif katılımını sağlayan, medikal bakımın uygulanmasını kolaylaştı-ran, diğer analjeziklerle kullanıldığında hastaların hastaneden kalış sürelerini azaltan, solunum fonksiyonlarına indirekt pozitif etkisi nedeniyle etkili öksürmeye katkıda bulunan, hastanın fiziksel fonksiyonel düzeyini geliştiren, kısaca cerrahi kazançlarını artıran ve iyileş-meyi hızlandıran, emniyetli ve etkili bir uygulama olarak kabul edilmektedir (58,59).…”
Section: Ağrı Kontrolüunclassified